EFEKTIVITAS STRATEGI EXAMPLES NONEXAMPLES DALAM MENINGKATKAN KEMAMPUAN MENULIS SURAT DINAS SISWA KELAS VIII SMP NEGERI 11 KOTA MAKASSAR - Supriadi Supriadi; Jayanti Sampara (Fakultas Keguruan dan Ilmu Penidikan UIM, 2018)
No result found for This study aims to examine the effectiveness of applying Nonexamples Examples strategies to improve the ability to write official letters for eighth grade students of SMP Negeri 11 Kota Makassar and to examine the differences in the effectiveness of student learning outcomes by using Nonexamples Examples with conventional models. The type of research used uses a quantitative approach to the method of expansion. The research variable consists of two namely the application of Nonexamples Examples strategy method as the independent variable X and learning to write official letters as the dependent variable Y. The research design used in this research is experimental research using quasi-experimental method with the initial test design and the final test of the control group and experimental group with random samples Therandomized pretest-posttest control design. The results of this study indicate that learning example non example is effective applied in learning to write official service this is based on the results of the calculation of the significance test which shows that the value of t counts is 51.015 t table value 2.021.This indicates that the proposed research hypothesis is accepted.Keywords: Nonexamples Examples Strategy Writing Service Letters.